SENP3-mediated deSUMOylation of Drp1 facilitates interaction with Mff to promote cell death - Guo, Chun (Sci Rep, 2017)
The GTPase dynamin-related protein 1 (Drp1) is essential for physiological and pathophysiological mitochondrial fission. DeSUMOylation of Drp1 by the enzyme SENP3 promotes cell death during reperfusion after ischaemia by enhancing Drp1 partitioning to the mitochondrial outer membrane (MOM), which causes cytochrome c release and apoptosis. However, how deSUMOylation recruits Drp1 to the MOM is unknown. Here we show that deSUMOylation selectively promotes Drp1 binding to the MOM resident adaptor protein mitochondrial fission factor (Mff). Consistent with this, preventing Drp1 SUMOylation by mutating the SUMO acceptor sites enhances binding to Mff. Conversely, increasing Drp1 SUMOylation by knocking down SENP3 reduces both Drp1 binding to Mff and stress-induced cytochrome c release. Directly tethering Drp1 to the MOM bypasses the need for Mff to evoke cytochrome c release, and occludes the effect of SENP3 overexpression. Thus, Drp1 deSUMOylation promotes cell death by enhancing Mff-mediated mitochondrial recruitment. These data provide a mechanistic explanation for how the SUMOylation status of Drp1 acts as a key switch in cell death/survival decisions following extreme cell stress.